AB0588 Prevalence of conventional cardiovascular risk factors in patients with psoriasis alone and in patients with psoriatic arthritis. (23rd January 2014) - Queiro-Silva, R.; Tejón, P.; Coto, P.; Alonso, S.; Alperi, M.; Rodríguez, S.; Acasuso, B.; Riestra, J. L.; Arboleya, L.; Ballina, J.
Abstract : Background: Patients with psoriasis and psoriatic arthritis (PsA) are at increased risk of cardiovascular disease. It has been suggested that this elevated risk reflects an increased prevalence of conventional cardiovascular risk factors in psoriatic patients. However, PsA may act as a confounder in this type of studies. Very few papers have studied the prevalence of such comorbidities in patients with psoriasis alone compared to those with PsA. Objectives: The main purpose of this study was to compare the profile of conventional cardiovascular risk factors in patients with psoriasis alone and in patients with PsA in order to analyze whether the presence of arthritis was associated with greater cardiovascular comorbidity. Methods: we analyzed the conventional cardiovascular risk profile (smoking, obesity, hypertension, diabetes mellitus and dyslipidemia) in 310 psoriatics (mean age 46 ± 15.6 years) and 86 PsA patients (mean age 49 ± 12.5 years). The study population was stratified according to sex, age at psoriasis onset, psoriasis severity, and HLA-Cw6. Uni and multivariate analyses were done in order to compare these factors with disease subtypes. Results: The global prevalence of cardiovascular risk factors was as follows: hypertension 20%, dyslipidemia 15.15%, obesity 30%, smoking 33.8%, DM II 9.3%. A total of 24 patients developed angor and/or myocardial infarction (6%). Compared to patients with psoriasis alone, those with PsA had a greater prevalence of DM II (11.8% vs. 8.8%, p=0.022) and a tendency towards higher levels of dyslipidemia (21.2% vs. 13.7%, p=0.08). Men had lower levels of HDL (49 ± 12.5 mg/dl vs. 59 ± 15.6 mg/dl, p< 0.05), higher levels of triglycerides (142 ± 86.4 mg/dl vs. 107 ± 67.8 mg/dl, p< 0.05), a higher abdominal circumference (101 ± 11.4 cm vs. 91 ± 14.12 cm, p< 0.05), and a higher BMI (29 ± 4.17 vs. 27 ± 5.09, p< 0.05). Subjects with disease onset over 40 years had a higher risk of developing DM II (OR 2.6, CI 95%: 1.14-5.93, p= 0.022). However, after adjusting for other factors this risk was higher among PsA subjects (OR 14, CI 95%: 1.73-112.5, p= 0.013). Patients carrying the HLA-Cw6 antigen showed less hypertension compared to those without this antigen (13.7% vs. 23.2%, p= 0.025). Similarly, patients with PASI < 10 showed more frequently hypertension than those with PASI >10 (22.3% vs. 15.5%, p=0.08). Conclusions: The profile of conventional cardiovascular risk factors differs between patients with psoriasis and PsA. Subjects with PsA had a higher risk of developing DM II, especially those with psoriasis onset above 40 years. Disclosure of Interest: None Declared